Update on management of polycystic ovarian syndrome for dermatologists - Shalini Gainder; Bharti Sharma (Wolters Kluwer Medknow Publications, 2019)
Polycystic ovarian syndrome (PCOS) is the commonest endocrine disorder in women having wide range of clinical manifestation. These women may present with reproductive, dermatological, metabolic, psychological, or neoplastic implications from adolescence to menopause. The common dermatological manifestations include hirsutism, acne, alopecia, or acanthosis nigricans. Women presenting with these dermatological manifestations must be evaluated for PCOS. A multidisciplinary team approach involving a reproductive endocrinologist, dermatologist, psychologist/psychiatrist, dietician, and sometimes a bariatric surgeon should be undertaken for long-term management of these patients. Unless metabolic and underlying endocrinal disturbances arecorrected and simultaneous life-style modification is adopted, cosmetic treatment would give only temporary relief.